Post traumatic nasal tip reconstruction with frontonasal flap, about a case - Rivadeneira, Andrés (Revista Universidad de Guayaquil, 2015)
When it comes to nasal reconstruction, there are several alternatives that we can handle depending on such factors as casual agent, duration time, age of patient, extent, location, dimensions, benign or malignant, among or malignant, among others. It is necessary then, to make a complete assessment of the patient so that we can choose the surgical technique properly. We introduce now, this technique as an alternative of choice in the reconstruction of post traumatic in our Hospital Luis Vernaza. We have recognized the injury as the most common causative agent in our working environment. Knowing that everyday increases crime, wounds by firearms and knives, and this is related to our case, since one of the most affected areas is often the face, and about it; the nose. Patients frequently come to the emergency area with bruises and injuries of all kinds in facial region. Frontonasal flap in absence of significant comorbidities provides good coverage of the nasal tip and allows, as appropriate remodeling of the nose with the same thickness flap; it is necessary in other cases making enforcement of bone or cartilage grafts.